2005
DOI: 10.1017/s0265021505000578
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of the endotracheal tube, laryngeal mask airway and oesophageal-tracheal Combitube®. A 6-month comparative prospective study of acquisition and retention skills by medical students

Abstract: Learning and retention skills of medical students, in a mannikin, are more accentuated with the laryngeal mask airway and the Combitube than seen with an endotracheal tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
1
25
0
3
Order By: Relevance
“…105 Eight manikin studies with simulated cardiac arrest (LOE 5) 89,90,96,[112][113][114][115][116] and 8 manikin studies without simulated cardiac arrest showed that successful insertion rates and/or time to insertion or to ventilation for a variety of supraglottic airway devices were as good, or better than, for the tracheal tube (LOE 5). [117][118][119][120][121][122][123][124] Nine studies documented that when a supraglottic airway device is used as a rescue airway after failed tracheal intubation, most patients can be ventilated successfully with the supraglottic airway device (LOE 2 98,99,103 ; LOE 3 [125][126][127][128] ; LOE 5 107,129 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…105 Eight manikin studies with simulated cardiac arrest (LOE 5) 89,90,96,[112][113][114][115][116] and 8 manikin studies without simulated cardiac arrest showed that successful insertion rates and/or time to insertion or to ventilation for a variety of supraglottic airway devices were as good, or better than, for the tracheal tube (LOE 5). [117][118][119][120][121][122][123][124] Nine studies documented that when a supraglottic airway device is used as a rescue airway after failed tracheal intubation, most patients can be ventilated successfully with the supraglottic airway device (LOE 2 98,99,103 ; LOE 3 [125][126][127][128] ; LOE 5 107,129 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…In the previous study by Weksler N et al, CT had a mean insertion time of 18 s and PLMA of 20 s, the difference being statistically insignificant. [17] There was difference in definition of insertion time and ease of insertion between the studies. Different studies allowed different numbers of attempts as successful insertion (two to three) before considering it as a failure.…”
Section: Discussionmentioning
confidence: 98%
“…Como sucede con cualquier procedimiento o destreza clínica, el aprendizaje y mantención de la habilidad para intubar la tráquea depende de la práctica continua o mediante sesiones en laboratorios de destrezas clínicas 19,20 . Desafortunadamente, la exposición del alumno a distintas maniobras prácticas y su aprendizaje tutorial durante su carrera en pregrado es muy variable, determinando una heterogeneidad importante en la adquisición de la competencia entre alumnos de una misma generación, a pesar de que son sometidos a las mismas rotaciones y programas durante su carrera 20,21 . Actualmente, la evaluación de alumnos de medicina de último año está más orientada a certifi car aspectos cognitivos (teoría), y en la demostración de destrezas clínicas relacionadas con la entrevista clínica y examen físico durante los ECOEs.…”
Section: Discussionunclassified
“…Es necesario contar con mecanismos de enseñanza y evaluación que permitan establecer el grado de aprendizaje, logro de objetivos y sobretodo la mantención de habilidades, para poder objetivar que aquellas competencias clasifi cadas como objetivos terminales de la carrera efectivamente sean logradas durante la formación médica 22 . Los alumnos de medicina debieran contar durante su etapa formativa con instancias que les permitan desarrollar sus destrezas técnicas en ambientes adecuados, controlados, bajo estricta supervisión docente y que, adicionalmente les permitan adquirir o reforzar habilidades de liderazgo y dirección del equipo de apoyo en distinta situaciones clínicas que rodean el procedimiento en cuestión, objetivo que es mejor logrado utilizando escenarios de simulación en centros de entrenamiento de destrezas clínicas habilitados para estos efectos, con espacios curriculares protegidos y posibilidad de revisar el desempeño del alumno en forma diferida [21][22][23] . Las dependencias físicas así como los docentes involucrados en la enseñanza de destrezas clínicas deben estar alineados con los objetivos curriculares para optimizar los recursos económicos y humanos 23 .…”
Section: Discussionunclassified